Theodor Von Heuglin receipt - Heuglin, Theodor von, 1824-1876.
Receipt (1867 November 4) issued to von Heuglin by the Royal Geographical Society, Great Britain, for one of his books.
German-born African explorer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Royal Geographical Society (Great Britain); Explorers